1974
DOI: 10.1539/joh1959.16.23
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Toluene in Mouse Tissues

Abstract: Distribution of toluene in mouse tissues was investigated by the gas chromatographic measurement after injection of toluene and by radioactivity assay after injection of "C toluene. The results obtained are as follows. 1. The concentration of toluene measured by gas chromatography was in the descending order in the tissues : kidney, liver and cerebrum. Toluene decreased more slowly in the cerebrum. 2. Higher radioactivity in the cerebrum than in the blood and the highest in the adipose tissue were observed aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 5 publications
0
2
1
1
Order By: Relevance
“…The BBCR values of brain stem regions of rats found in the present study are relatively higher than those of whole brain given in previous reports (1.2-2.5) (Sato et al 1974;Pyykk6 et al 1977;Benignus et al 1984;Kishi et al 1988) and in mice (1.26-2.05) (Bruckner 1981;Ogata et al 1981). Since the brain stem contains various important vital centers for cardiac, vasomotor, respiratory and pneumotaxic function, toluene exposure may be lifethreatening from this point of view.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…The BBCR values of brain stem regions of rats found in the present study are relatively higher than those of whole brain given in previous reports (1.2-2.5) (Sato et al 1974;Pyykk6 et al 1977;Benignus et al 1984;Kishi et al 1988) and in mice (1.26-2.05) (Bruckner 1981;Ogata et al 1981). Since the brain stem contains various important vital centers for cardiac, vasomotor, respiratory and pneumotaxic function, toluene exposure may be lifethreatening from this point of view.…”
Section: Resultscontrasting
confidence: 74%
“…Hence, the regional toluene concentration in the brain is important. The brain/blood ratio of toluene in rats (Sato et al 1974;Pyykk6 et al 1977;Benignus et al 1984;Kishi et al 1988) and mice (Bruckner 1981;Ogata et al 1981), and the brain toluene concentrations in fatal human cases (Kashima et al 1969;Nomiyama and Nomiyama 1978;King et al 1981;Kojima et al 1982;Moffat 1986;Takeichi et al 1986;Matoba et al 1987;Ameno et al 1989;Baselt and Cravey 1989) have been reported, but not concentrations in the various brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…In the dog, the highest levels were found in the adrenals (Gerarde 1959). More recently, however, the highest concentrations at all times were found in the white adipose tissue (Carlsson and Lindqvist 1977, Koga 1978, Ogata et al 1974 followed by the kidneys, adrenals, liver and brain. Thus, the longest half-life values for toluene have been determined in adipose persons (Carlsson and Ljungquist 1982), a phenomenon which has also been observed in persons exposed to benzene.…”
Section: Uptake Biotransformation and Excretionmentioning
confidence: 97%
“…Beim Hund wurde der höchste Wert in den Nebennieren beobachtet [34]. In neuerer Zeit fand man dagegen zu allen Zeitpunkten die höchsten Konzentrationen im weißen Fett [35][36][37], gefolgt von Niere, Nebenniere, Leber und Hirn. So wurden auch die längsten Halbwertszeiten bei adipösen Probanden gemessen [38], ähnlich den Beobachtungen bei Benzol-Exposition.…”
unclassified